Investigation of Virulence Genes of Staphylococcus aureus Isolated from Sterile Body Fluid Samples and Their Correlation with Clinical Symptoms and Outcomes - Tao Lin; Qianhui Li; Defu Jin; Wanbo Liu; Chaogui Tang; Xiaoyun Zhang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Staphylococcus aureus is the major pathogen causing nosocomial human infections and produces a variety of virulence factors that contribute to its ability to colonize and cause diseases. This study was conducted to investigate the virulence genes in S. aureus isolated from sterile body fluid samples and their correlation with clinical symptoms and outcomes. The VITEK 2® Compact system was used to perform biochemical identification and antimicrobial susceptibility tests on 33 S. aureus isolates. Virulence genes were amplified using multiplex PCR. The virulence gene patterns were analyzed by systematic cluster analysis. The frequency of methicillin-resistant S. aureus was 45.45%, and 17 virulence genes were identified. Genes encoding hemolysins showed high frequencies. The frequencies of hla, hlb, hld, and hlgB were 93.94% and that of the luk-F/S-PV was 21.21%. Except for the frequency of splB (51.52%), the remaining genes encoding invasive proteases showed frequencies greater than 81.82%. Among the patients, 100.00% had undergone invasive medical procedures and 24.00% had been treated with more than three types of antibiotic drugs. Invasive medical procedures are the main causes of infection. Resistance to antibiotic drugs and the status of carrying virulence genes were highly related to clinical symptoms and outcomes.